The Shared Foundations of Faith in Christianity and Islam: The Role of Monotheism in Life and Afterlife Across Abrahamic Religions - Adeoye, Moses Adeleke (At-Turost : Journal of Islamic Studies, 2024)
This discourse explores the relationship between Christianity and Islam, two of the world's largest Abrahamic faiths, and their shared foundations rooted in monotheism. Despite theological divergences, both faiths converge on fundamental beliefs that shape their followers' understanding of life and the afterlife. Monotheism serves as a foundational principle that delineates God's character, and influences moral conduct, community bonding, and eschatological expectations. The paper delineates how both religions articulate their conception of God as the singular, all-powerful creator, emphasizing the implications this has for believers in their daily lives and spiritual practices. It examines the ethical frameworks established by both faiths, reflecting on how monotheistic belief systems promote values such as compassion, justice, and accountability. The discourse also discusses the commonality of prophetic traditions within Christianity and Islam, highlighting figures such as Abraham, Moses, and others who serve as pivotal links between the two faiths. The role of scripture, particularly the Bible and the Quran, is discussed as a means through which divine guidance is conveyed, reinforcing the importance of faith in navigating life's challenges and moral dilemmas faced by believers. In a contemporary context marked by religious pluralism and interfaith dialogue, this research emphasizes the need for a deeper understanding of these shared foundations to promote mutual respect and coexistence among diverse religious communities.